2018
DOI: 10.1111/pirs.12235
|View full text |Cite
|
Sign up to set email alerts
|

Urban subcentres in German city regions: Identification, understanding, comparison

Abstract: Whereas many studies exist regarding urban subcentre identification, systematic analyses of these methods' characteristics are scarce. This paper addresses and reflects these issues for one selected method, the locally weighted regression (LWR) approach. Methodologically the study concludes that no ‘one size fits all’ method exists, but that the LWR is a sensitive means to identify urban subcentres. Content‐wise the study finds that German city regions are fairly monocentric, as all identified subcentres are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 64 publications
(130 reference statements)
1
17
1
Order By: Relevance
“…This is in contradiction to the findings of Schmidt et al (2018), who found that central places per capita were consistently significant in explaining urbanisation patterns at the regional level. However, it is in line with Krehl (2018), who finds evidence for the continued monocentric nature of German city regions. Similarly, average price of land was significant for this study, but was not significant according to Schmidt et al (2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in contradiction to the findings of Schmidt et al (2018), who found that central places per capita were consistently significant in explaining urbanisation patterns at the regional level. However, it is in line with Krehl (2018), who finds evidence for the continued monocentric nature of German city regions. Similarly, average price of land was significant for this study, but was not significant according to Schmidt et al (2018).…”
Section: Discussionsupporting
confidence: 89%
“…The number of central places per capita, our proxy to capture polycentricity, was not significant in any of the models, contrary to the findings of Schmidt et al (2018). That said, the implication that German metropolitan areas are fairly monocentric is in line with Krehl (2015Krehl ( , 2018 and Knapp and Volgmann (2011). Krehl (2018: 90f.…”
Section: Cross-sectional Estimatesmentioning
confidence: 82%
“…Urban regions are undoubtedly complex, which especially applies to urban spatial structure representing the distribution of human activities (e.g., Angel & Blei, 2016, Craig, Kohlhase, & Perdue, 2016, Parr, 2014, Scott & Storper, 2015, Spencer, 2015, Yang, French, Holt, & Zhang, 2012. Whereas several studies analyze metropolitan areas as two-dimensional geographic spaces, that is, in the sense of identifying urban and suburban densifications of economic activity (e.g., Arribas-Bel, Ramos, & Sanz-Gracia, 2015, Giuliano & Small, 1991, Krehl, 2018, McMillen, 2001, Riguelle et al, 2007, examining the multidimensionality of metropolitan areas' urban spatial structure has mainly been done with theory-led, quantitative means of analysis (e.g., Adolphson, 2010, Appold, 2015, Arribas-Bel & Sanz-Gracia, 2014, Roca Cladera, Marmolejo Duarte, & Moix, 2009. Within these and similar contributions, much work has been devoted to theoretical and empirical aspects of the distribution of socioeconomic activity and land uses.…”
Section: State Of Researchmentioning
confidence: 99%
“…Compared to the above-mentioned contributions regarding conceptual issues, further studies consider selected characteristics of urban centers and subcenters. These studies can be subdivided into studies that either discuss certain characteristics of subcenters, such as their location within a metro (e.g., Einig & Guth, 2005, Krehl, 2015McMillen & Lester, 2003), or these subcenters' region-wide relevance to population density, employee density or land prices (e.g., Arribas-Bel & Sanz-Gracia, 2014, Craig et al, 2016, Krehl, 2018, McMillen, 2001. Concerning the locations of subcenters, it can be concluded that they are often located in close proximity to the regional center and, in Germany at least, rarely in peripheral areas (Krehl, 2015(Krehl, , 2018.…”
Section: State Of Researchmentioning
confidence: 99%
See 1 more Smart Citation